Idiopathic inflammatory myopathies. (February 2018) - Parker, Matthew J.S.; Lilleker, James B.; Roberts, Mark E.; Chinoy, Hector
Abstract: Idiopathic inflammatory myopathies represent a rare group of diseases characterized by a central role of autoimmune processes and the inflammation of skeletal muscle. There has been significant recent progress in understanding disease pathogenesis, phenotyping subtypes of disease and investigating effective therapeutic options. Patients typically present with progressive, proximal weakness and functional impairment, and elevated muscle enzymes. There can also have extramuscular manifestations, including skin, respiratory, articular, gastrointestinal and cardiovascular involvement, which can precede or occur in the absence of clinically detectable muscle involvement. There are therefore a multitude of potential differential diagnoses to consider. A conscientious initial evaluation supported by pragmatically structured investigations remains critical to accurate diagnosis and appropriate management of these complex conditions.